2021
DOI: 10.1371/journal.pone.0253834
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical aspects of Thai fermented fish viscera, Tai-Pla, curry powder processed by hot air drying and hybrid microwave-infrared drying

Abstract: The objective of this research was to comparatively investigate the effect of hot air drying (HA) and hybrid microwave-infrared drying (MI) on physico-chemical characteristics of Thai fermented fish viscera, Tai-Pla, curry powder (TCP). HA was carried out at 60°C, 70°C, and 80°C and MI was carried out at a microwave power of 740, 780, and 810 W with a constant infrared heating power (500 W) for different drying times to obtain the final moisture content ≤ 12.0% and the water activity (aw) ≤ 0.6. The quality ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Choopan et al . (2021) reported that free amino acids and other soluble non‐nitrogenous substances derived from Tai‐Pla (fermented fish viscera) sauce and fermented shrimp paste, as sources of protein, could serve as nutrients supporting microorganism growth until 1 × 10 4 CFU g −1 sample.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Choopan et al . (2021) reported that free amino acids and other soluble non‐nitrogenous substances derived from Tai‐Pla (fermented fish viscera) sauce and fermented shrimp paste, as sources of protein, could serve as nutrients supporting microorganism growth until 1 × 10 4 CFU g −1 sample.…”
Section: Resultsmentioning
confidence: 99%
“…Kaeng‐Tai‐Pla‐Haeng was prepared by the red curry paste mixed with shrimp paste and mackeral meat, then heated with water together with Tai pla sauce until it boiled and let the water evaporate until the water activity was approximately 0.85. (Choopan et al ., 2021), and then divided into four groups. A freeze‐dried supernatant of L. plantarum 124 at its MIC was supplemented in Kaeng‐Tai‐Pla‐Haeng , which was expected to inhibit fungal spoilage growth.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations